A novel technique for reducing lead-time and energy consumption in fabrication of Inconel-625 parts by laser-based metal deposition process. Issue 2 (21st March 2016) - Vinod, A.R.; Srinivasa, C.K.; Keshavamurthy, R.; Shashikumar, P.V.
Abstract : Purpose: This paper aims to focus on reducing lead-time and energy consumption for laser-based metal deposition of Inconel-625 superalloy and to investigate the effect of process parameters on microstructure, density, surface roughness, dimensional accuracy and microhardness. Design/methodology/approach: Inconel material was deposited on steel substrate by varying process parameters such as laser power, laser scan speed and powder flow rate. The deposited parts were characterized for their density, surface roughness, dimensional accuracy and microhardness. Findings: The study reveals that with increase in laser power, laser scan speed and powder flow rate, there was an increase in density, surface roughness values and microhardness of the deposits, while there was a decrease in dimensional accuracy, deposition time and energy consumption. Practical implications: The results of this study can be useful in fabrication of Inconel components by laser-based metal deposition process, and the methodology can be expanded to other materials to reduce the lead-time and energy consumption effectively. Originality/value: The present study gives an understanding of effect of process parameters on density, surface roughness, dimensional accuracy, microhardness, deposition time and energy consumption for laser-based metal deposition of Inconel-625.